See Photography as a Visual Art Storing - Aryo Bayu Wibisono; Aphief Tri Artanto; Alfian Ayuswantana (Nusantara Science and Technology Proceedings, 2020)
Photography in today's era is a device that is always there and used by every human being. Before the emergence of photography techniques, the media was dominated by illustration techniques used for story media with graphic novels or comics. However, over time, photography was also able to perform digital engineering schemes to create visual models and illustration techniques, but it was not popular. To support the development of photography techniques in various fields, a continuous discussion is needed so that each research can define photography as a technique to convey messages, especially in media that require pictorial stories. This research stage will reveal the initial stages and the factors that can be applied in further research. Therefore, this research is classified as a descriptive study as the initial discussion of the research. This study will use a qualitative approach by collecting literature observation data and comparing selected visual samples.